Map4k4 suppresses Srebp-1 and adipocyte lipogenesis independent of JNK signaling[S] - Laura V. Danai (Journal of Lipid Research, 2013)
Adipose tissue lipogenesis is paradoxically impaired in human obesity, promoting ectopic triglyceride (TG) deposition, lipotoxicity, and insulin resistance. We previously identified mitogen-activated protein kinase kinase kinase kinase 4 (Map4k4), a sterile 20 protein kinase reported to be upstream of c-Jun NH2-terminal kinase (JNK) signaling, as a novel negative regulator of insulin-stimulated glucose transport in adipocytes. Using full-genome microarray analysis we uncovered a novel role for Map4k4 as a suppressor of lipid synthesis. We further report here the surprising finding that Map4k4 suppresses adipocyte lipogenesis independently of JNK. Thus, while Map4k4 silencing in adipocytes enhances the expression of lipogenic enzymes, concomitant with increased conversion of 14C-glucose and 14C-acetate into TGs and fatty acids, JNK1 and JNK2 depletion causes the opposite effects. Furthermore, high expression of Map4k4 fails to activate endogenous JNK, while Map4k4 depletion does not attenuate JNK activation by tumor necrosis factor α. Map4k4 silencing in cultured adipocytes elevates both the total protein expression and cleavage of sterol-regulated element binding protein-1 (Srebp-1) in a rapamycin-sensitive manner, consistent with Map4k4 signaling via mechanistic target of rapamycin complex 1 (mTORC1). We show Map4k4 depletion requires Srebp-1 upregulation to increase lipogenesis and further show that Map4k4 promotes AMP-protein kinase (AMPK) signaling and the phosphorylation of mTORC1 binding partner raptor (Ser792) to inhibit mTORC1. Our results indicate that Map4k4 inhibits adipose lipogenesis by suppression of Srebp-1 in an AMPK- and mTOR-dependent but JNK-independent mechanism.